Morphological development and oxidation of elongated β-SiAlON material - Hou X.-M.; Yue C.-S.; Singh A.K.; Zhang M.; Chou K.-C. (My University, 2025)
Elongated β-SiAlON whiskers and ribbons have been synthesized at 1700. K under flowing nitrogen atmosphere. A series of experiments have been performed using thermogravimetry (TG) and thermal field emission scanning electron microscope (FE-SEM) to investigate its oxidation resistance. The results showed that the synthesized β-SiAlON material possessed good oxidation resistance and the shape can be well kept up to 1373. K. Chou's model has been used to investigate the oxidation kinetics, from which it was concluded that β-SiAlON in shape of ribbons has better oxidation resistance than that in shape of whisker from the view point of a new index of the characteristic oxidation time. © 2011 Elsevier Ltd.